2016
DOI: 10.1111/bjd.14403
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase 2b trial of baricitinib, an oral Janus kinase (JAK) 1/JAK2 inhibitor, in patients with moderate‐to‐severe psoriasis

Abstract: SummaryBackground Plaque psoriasis is a chronic and often debilitating skin disorder and proinflammatory cytokines are known to play a key role in the disease process. Objectives To evaluate the safety and efficacy of baricitinib, an oral Janus kinase (JAK) 1/JAK2 inhibitor, in patients with moderate-to-severe psoriasis in a randomized, double-blind, placebo-controlled, dose-ranging phase 2b study. Methods Patients were randomized (n = 271) to receive placebo or oral baricitinib at 2, 4, 8 or 10 mg once daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
168
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(190 citation statements)
references
References 30 publications
5
168
0
3
Order By: Relevance
“…In this 12 week dose ranging study, patients treated with 8mg and 10mg once daily achieved PASI 75 responses of 43% and 54% respectively 11 .…”
Section: Psoriasismentioning
confidence: 86%
See 2 more Smart Citations
“…In this 12 week dose ranging study, patients treated with 8mg and 10mg once daily achieved PASI 75 responses of 43% and 54% respectively 11 .…”
Section: Psoriasismentioning
confidence: 86%
“…Baricitinib, still in clinical trials and not yet FDA approved for any condition, was recently reported to be efficacious in moderate-to-severe plaque psoriasis in a phase 2b trial 11 . In this 12 week dose ranging study, patients treated with 8mg and 10mg once daily achieved PASI 75 responses of 43% and 54% respectively 11 .…”
Section: Psoriasismentioning
confidence: 99%
See 1 more Smart Citation
“…17 A phase 2 trial suggests that baricitinib may offer similar efficacy in patients with moderate to severe plaque psoriasis. 18 Topical formulations of JAK inhibitors have also been evaluated; early trials suggest that ruxolitinib compares well with established topical treatments but trials of topical tofacitinib have been inconclusive. 13 Other early trials suggest that JAK inhibitors show promise in the treatment of vitiligo and atopic dermatitis.…”
Section: Dermatologymentioning
confidence: 99%
“…These results are implying to the high potential of JAK inhibitors to treating AA disease. Although there is no study on safety of these drugs in AA patients, no serious safety concern associated with the use of baricitinib was reported in rheumatoid arthritis and psoriasis patients [9,10]. In addition to JAK inhibitors, fontolizumab, an anti-IFN-c may be another novel biological treatment of AA, which needs for further studies, associated with its efficiency and safety in patients with AA.…”
Section: To the Editormentioning
confidence: 99%